Les « coups de foudre » de Jupiter et l’exportation de la religion romaine en Gaule - Nicolas Laubry (Gallia)
The practice of burying or enclosing the fulgur is better attested in south-eastern Gaul than in any other province of the Western Roman Empire. The presence of this ritual of Roman origin has generally been connected to a supposed pre-Roman lightning cult which would have continued in that way during the Principate, especially in the countryside as a consequence of a form of syncretism favoured by its inhabitants. However, confronting the Gallic documentation with written sources and evidence for this ritual in Italy helps to consider these inscriptions in a different way. Implying the transmission of a specific knowledge, the adoption of this practice raises the question of the vehicles of diffusion. It could also have relationships with a redefinition of collective religion in the frame of the cities establishment in the Roman period, and consequently inform on transfer modalities of some gestures and ritual knowledge from Italy to Gaul.